2007
DOI: 10.1262/jrd.19064
|View full text |Cite
|
Sign up to set email alerts
|

The Perivitelline Space-Forming Capacity of Mouse Oocytes is Associated with Meiotic Competence

Abstract: Abstract. Although mouse oocytes progressively acquire meiotic competence during their growth in the ovaries, only half of full-grown oocytes can accomplish meiosis. Two types of full-grown oocytes have been reported on the basis of their chromatin configuration, the surrounded-nucleolus (SN) type and the non-surrounded-nucleolus (NSN) type. Therefore, full-grown oocytes collected from the ovaries of adult animals comprise a heterogeneous population; some oocytes are meiotically incompetent (NSN-type), and som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 44 publications
0
29
0
Order By: Relevance
“…The SN conformation of oocyte chromatin was reported to correlate with developmental potential of the oocytes, both in terms of completing meiotic maturation as well as promoting embryonic development after fertilization (ZUCCOTTI et al 1998;INOUE et. al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The SN conformation of oocyte chromatin was reported to correlate with developmental potential of the oocytes, both in terms of completing meiotic maturation as well as promoting embryonic development after fertilization (ZUCCOTTI et al 1998;INOUE et. al.…”
Section: Discussionmentioning
confidence: 99%
“…Another approach was reported by Inoue and colleagues (INOUE et al 2007) who found that antral oocytes with SN configuration and high developmental competences develop perivitelline space upon one hour of incubation in the culture. This method is less complicated and time consuming and gives significant enrichment of the SN fraction from 64% in the whole population to 91% in oocytes which form the perivitelline space.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By the time they develop into mature MII eggs, oocytes have developed a perivitelline space (PVS) between the oocyte plasma membrane and zona pellucida (Dandekar and Talbot, 1992;Talbot and Dandekar, 2003). Although the development of the PVS had been largely assumed to be the result of the loss of oocyte volume to the first polar body, the PVS actually develops well before the extrusion of the first polar body and also develops in oocytes maintained in GV arrest that do not form a polar body (Inoue et al, 2007). Consistent with this, direct measurements indicated that oocyte volume decreases in vivo by about 20% within 8 hr after ovulation is triggered, reaching a minimum just before first polar body emission (Tartia et al, 2009).…”
Section: Volume Regulation Before Fertilizationmentioning
confidence: 99%